2015
DOI: 10.1155/2015/459428
|View full text |Cite
|
Sign up to set email alerts
|

Binary Logistic Regression Analysis of Foramen Magnum Dimensions for Sex Determination

Abstract: Purpose. The structural integrity of foramen magnum is usually preserved in fire accidents and explosions due to its resistant nature and secluded anatomical position and this study attempts to determine its sexing potential. Methods. The sagittal and transverse diameters and area of foramen magnum of seventy-two skulls (41 male and 31 female) from south Indian population were measured. The analysis was done using Student's t-test, linear correlation, histogram, Q-Q plot, and Binary Logistic Regression (BLR) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
(45 reference statements)
4
26
1
2
Order By: Relevance
“…Although some studies suggested these did not have a correlation with the sagittal and the transverse diameter of the FM [43], other studies reported a sexual dimorphism for FM dimensions with all parameters being significantly higher in males [44]. Kamath et al [45] found sex predictability (higher values in males) for FM area (70.3%), followed by sagittal diameter (69.6%), and least for transverse diameter (66.4%), similar to the study of Uthman et al [46] for FM area and Raghavendra Babu et al [47] with higher predictability for FM area and sagittal diameter compared to transverse diameter [9]. Rai et al [48] found OC and FM dimensions higher in males compared to females No stastistically significant difference was found in adults for different age groups for the OC [49] and FM [50].…”
Section: Far Lateral Approachmentioning
confidence: 97%
“…Although some studies suggested these did not have a correlation with the sagittal and the transverse diameter of the FM [43], other studies reported a sexual dimorphism for FM dimensions with all parameters being significantly higher in males [44]. Kamath et al [45] found sex predictability (higher values in males) for FM area (70.3%), followed by sagittal diameter (69.6%), and least for transverse diameter (66.4%), similar to the study of Uthman et al [46] for FM area and Raghavendra Babu et al [47] with higher predictability for FM area and sagittal diameter compared to transverse diameter [9]. Rai et al [48] found OC and FM dimensions higher in males compared to females No stastistically significant difference was found in adults for different age groups for the OC [49] and FM [50].…”
Section: Far Lateral Approachmentioning
confidence: 97%
“…In addition, foramen magnum morphometry is relevant in forensic medicine. For example, sex determination based on foramen magnum morphometry, albeit limited to some extent, is useful (Günay & Altinkök, 2000;Suazo et al, 2009;Ukoha et al, 2011;Edwards et al, 2013;Kamath et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This might be the result of variables affecting the bone physiology, such as the ethnic miscegenation in the Brazilian population [5,23] or differences in the socioeconomic profile of the individuals [24], which were not taken into consideration here. Despite this, the morphological characteristics of the incisor canal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, one can find that there was a gradual increase in the mean values for both male and female patients regarding antero-posterior diameter, as shown in figures 5 and 6, except the laterolateral diameter in the former as there was a decrease in the mean value observed in Group III ( Figure 6). Nevertheless, due to these overlaps, we recommend the use of the opening diameter of incisor foremen with caution as a method for age estimation and, if possible, in association with other parameters [3,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation